Ablation efficiency of gold at fs/ps laser treatment in water and air. (13th January 2022) - Smirnov, N A; Kudryashov, S I; Rudenko, А А; Nastulyavichus, A A; Ionin, A A
Abstract: A comparison of single-pulse laser ablation of gold target by pulses with a 0.3–10 ps duration and a wavelength of 515 nm in air and in water was performed. The radiation was focused on the sample surface through the objectives with numerical apertures NA = 0.65 and 0.25. The influence of the medium, pulse duration, and spot size on the crater morphology was studied. A significant difference in crater morphology was found for different lenses. The ablation efficiency was studied by measuring the profiles of single-shot pulse craters using scanning force microscopy. The contribution of filamentation to the ablation process is shown quantitatively.